Effects of adverse fertility-related factors on mitochondrial DNA in the oocyte: a comprehensive review - Wenying Zhang; Fuju Wu (BMC, 2023)
Abstract The decline of oocyte quality has profound impacts on fertilization, implantation, embryonic development, and the genetic quality of future generations. One factor that is often ignored but is involved in the decline of oocyte quality is mitochondrial DNA (mtDNA) abnormalities. Abnormalities in mtDNA affect the energy production of mitochondria, the dynamic balance of the mitochondrial network, and the pathogenesis of mtDNA diseases in offspring. In this review, we have detailed the characteristics of mtDNA in oocytes and the maternal inheritance of mtDNA. Next, we summarized the mtDNA abnormalities in oocytes derived from aging, diabetes, obesity, and assisted reproductive technology (ART) in an attempt to further elucidate the possible mechanisms underlying the decline in oocyte health. Because multiple infertility factors are often involved when an individual is infertile, a comprehensive understanding of the individual effects of each infertility-related factor on mtDNA is necessary. Herein, we consider the influence of infertility-related factors on the mtDNA of the oocyte as a collective perspective for the first time, providing a supplementary angle and reference for multi-directional improvement strategies of oocyte quality in the future. In addition, we highlight the importance of studying ART-derived mitochondrial abnormalities during every ART procedure.